COMPARISON OF WORKING TIME IN PLACEMENT OF CONVENTIONAL MATRIX VS PRE CONTOURED MATRIX (Cuestiones de Fisioterapia, 2022)
In clinical practice, obtaining physiologic proximal contact points is essential for protection of balance and harmony of the stomatognathic system. This study aimed at assessing the influence of different matricing techniques; either sectional matrix or circumferential matrix in undergraduate students